2012
DOI: 10.1063/1.3671997
|View full text |Cite
|
Sign up to set email alerts
|

Free energy profiles for penetration of methane and water molecules into spherical sodium dodecyl sulfate micelles obtained using the thermodynamic integration method combined with molecular dynamics calculations

Abstract: Free energy profiles for penetration of methane and water molecules into spherical sodium dodecyl sulfate micelles obtained using the thermodynamic integration method combined with molecular dynamics calculations K. Fujimoto Science, Nagoya University, Japan (Received 14 October 2011; accepted 5 December 2011; published online 6 January 2012) The free energy profiles, G(r), for penetration of methane and water molecules into sodium dodecyl sulfate (SDS) micelles have been calculated as a function of distan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 37 publications
(34 reference statements)
1
18
0
Order By: Relevance
“…In our previous works, [15][16][17][18] two extremes of solubilization of water and hydrocarbons were investigated. First, we performed molecular dynamics (MD) calculations and found that the free energy of transfer of a water molecule from bulk water to sodium dodecyl sulfate (SDS) micelle has a large positive value, +28 kJ mol −1 , and that the water molecule is seldom contained in the SDS micelle.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous works, [15][16][17][18] two extremes of solubilization of water and hydrocarbons were investigated. First, we performed molecular dynamics (MD) calculations and found that the free energy of transfer of a water molecule from bulk water to sodium dodecyl sulfate (SDS) micelle has a large positive value, +28 kJ mol −1 , and that the water molecule is seldom contained in the SDS micelle.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2 shows the potential of mean force W(R) as a function of the distance R of the solute center of mass from the micellar center. The hydrophobic solute is stabilized at the center of micelle compared to the aqueous region [1,7,11,12], and is more so when the restraint is stronger (k of Eq. (1) is larger).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows the probability distribution function thus determined. When k = 0 and no restraint is applied to the micelle, the solute is most likely to stay in the outer portion of the hydrophobic-tail region (R ≈ 15Å) and distributes diffusely toward the center of micelle [7,11,12,28,29]. At k = 0, indeed, the potential of mean force presented in Figure 2 varies by ∼1 kcal/mol within the hydrophobic-tail region, and the probability in Figure 3 is larger in the outer portion due to the presence of the R 2 factor in Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrolysis is important for chemical decomposition in which the compounds are spitted into smaller compounds by reacting with water. Hydrolysis of protein under controlled condition generates peptides, and thus the functional properties of a protein is improved (Fujimoto et al 2012). So, a proper hydrolysis technique at suitable and optimum conditions plays an important role in industrial bio-functional food preparations.…”
Section: Introductionmentioning
confidence: 99%